The SuperDARN’s role in ion-neutral coupling research - Billett, Daniel D.; McWilliams, Kathryn A. (Polar Science, 2021)
The direct collisions that thermospheric neutral particles experience with convecting ionospheric ions is the primary way in which energy from the solar wind is deposited into the Earth’s atmosphere. Because of these collisions, the neutral gas polewards of middle latitudes ( geomagnetic) is often set into motion due to ion-drag, and Joule heated due to friction. Transient ionospheric phenomena, such as auroral arcs and sub-auroral polarisation streams (SAPS) also modify neutral winds in their own distinctive way. Thanks to the large spatial coverage of the Super Dual Auroral Radar Network (SuperDARN) at both middle and high latitudes, studies into ionosphere–thermosphere coupling have been enabled. These range from collaborative studies with neutral wind measurements from other instruments, to the driving electrodynamic input of various global circulation models. This paper aims to provide a general overview of the ion-neutral coupling research conducted utilising the SuperDARN, and to offer some directions as to where we believe future work should be directed. journal article